New developments in our understanding of psoriatic arthritis and their impact on the diagnosis and clinical management of the disease. (1st August 2013) - Boehncke, W.H.; Kirby, B.; FitzGerald, O.; van de, P.C.M.
Abstract Psoriatic arthritis (PsA) is a spondyloarthritis with a comorbid association with psoriasis. Without appropriate treatment it can be progressive, severe, deforming and destructive. It has long been recognized that subsets of PsA patients exist, characterized by different patterns of joint involvement. Associations between development of PsA and certain human leukocyte antigens (HLA) have been established. Evidence now suggests that progression of PsA is also genetically determined. The presence of one allele (HLA‐B*27) has been associated with a distinct phenotype characterized by early joint involvement, whereas development of musculoskeletal symptoms is much slower in patients with another allele, C*06. Dermatologists need to consider what these differences in genotypes and phenotypes mean for clinical practice. Delay in the diagnosis of PsA is a significant contributor to poor patient outcomes, but there is evidence that PsA is underdiagnosed among psoriasis patients attending dermatology clinics. Dermatologists need to identify PsA symptoms among their psoriasis patients and refer for rheumatological assessment where appropriate. Treatment should address all aspects of the disease, including skin, nail and joint symptoms as well as physical functioning and quality of life. The existence of distinct phenotypic and genetic PsA subsets means dermatologists need to consider which drugs are likely to be most efficacious in which patient populations. Stratification of PsA according to susceptibility genes may in future help identify patients requiring more aggressive treatment to prevent progression. Biologic therapies show efficacy in PsA, but the patient populations of clinical trials are not always representative of patients treated with biologics in clinical practice.